2004
DOI: 10.1016/j.labeco.2003.09.002
|View full text |Cite
|
Sign up to set email alerts
|

The relative efficiency of labor market programs: Swedish experience from the 1990s

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
80
0
9

Year Published

2006
2006
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(90 citation statements)
references
References 12 publications
1
80
0
9
Order By: Relevance
“…The role of public employment as a stabilizer during periods of low labor demand was, thereby, undermined; temporary public programs beyond short-term participation are ineffective, and participation may actually lower employment probability and Rodriguez-Planas and Benus (2008) for more recent analyses. Furthermore, the lack of usefulness of public works in generating medium-to longer-run effects is supported by Carling and Richardson (2004) as well as Sianesi (2008), who conclude in their evaluations that the closer an ALMP is to regular work the better its effects for the participants. The evidence from Autor and Houseman (2010) from Detroit's Work First program cleary underlines the relevance of regular work experience for employment and earnings.…”
Section: Incentives For Seeking and Keeping A Job (Category Iii)mentioning
confidence: 97%
See 1 more Smart Citation
“…The role of public employment as a stabilizer during periods of low labor demand was, thereby, undermined; temporary public programs beyond short-term participation are ineffective, and participation may actually lower employment probability and Rodriguez-Planas and Benus (2008) for more recent analyses. Furthermore, the lack of usefulness of public works in generating medium-to longer-run effects is supported by Carling and Richardson (2004) as well as Sianesi (2008), who conclude in their evaluations that the closer an ALMP is to regular work the better its effects for the participants. The evidence from Autor and Houseman (2010) from Detroit's Work First program cleary underlines the relevance of regular work experience for employment and earnings.…”
Section: Incentives For Seeking and Keeping A Job (Category Iii)mentioning
confidence: 97%
“…Various reviews of studies around the world ) focused on OECD countries , and especially evaluations for Sweden (Sianesi, 2008;Carling and Richardson, 2004), highlight that private sector hiring subsidies can generally be more effective in benefiting the targeted workers by bringing them into employment than public education and training measures or public works Evidence for various countries shows that hiring subsidies outperform other ALMPs in terms of post program employability 70 . A survey by Neumark (2013) of US evidence highlights that, using unfavorable estimates, hiring subsidies are at least more than twice as effective as public job creation.…”
Section: Incentives For Creating Employment (Category Ii)mentioning
confidence: 99%
“…They showed that participants had much higher subsequent employment rates than similar unemployed persons, who did not take up a subsidized job. Likewise, evidence for Britain (Dorsett 2006) and Sweden (Sianesi 2008;Carling and Richardson 2004;Fredriksson and Johansson 2008;Forslund et al 2004) suggested that wage subsidies had a positive effect on employment probabilities of the participants. Turning to the few results from social experiments on subsidy vouchers, Burtless (1985) found that unemployed persons with a voucher were less likely to find employment than job-seekers without vouchers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…For business start-up programs in Sweden, we refer to Carling and Gustafson (1999). For training measures comprising formal qualification, further training of any kind, and retraining, see Richardson and van den Berg (2001) and Carling and Richardson (2004) for Sweden and Gerfin and Lechner (2002) and Hujer et al (2005) for Switzerland and Germany. investigate long-run effects for Germany.…”
Section: Introductionmentioning
confidence: 99%